Military-bureaucracy brinksmanship - Raghavan, Srinath (2016)
There is a widening civil-military "gap" in India today which stems from developments on both sides of the divide. The liberalisation and rapid growth of the Indian economy over the last 25 years have considerably increased the gap between the economic profiles of the civilian and military personnel. - Reproduced.
Keywords: Bureaucracy; Defence